A Comparative Study between Extrovert and Introvert Students’ on Writing Achievement - Sirajuddin, Sry Rezki Ayu; Salija, Kisman; Halim, Abd. (Har Press Indonesia, 2023)
In line with the objective of this study is to provide a descriptive account of the student's achievement. Students have better writing achievement. In this study, the researcher uses comparative research. The population of this research will be the students in SMP Negeri 1 Barru in the 2022/2023 academic year and the total population is 129 students. The research participants in this study were the students of SMP Negeri 1 Barru. A random class method is employed to select the 31 participants. This is evidenced by the t count t-test (-,0426) which is lower than the ttable (1,69913) at a significance level of 0.05. Thus, the hypothesis (H1) is accepted and null (H0) is rejected. In a comparative study between the personality of extrovert and introvert students, there is a significant difference between the personality of extrovert and introvert students in writing achievement. However, it can be seen from the average personality value of extrovert students (83.15) is higher than the personality of introvert students (78.83) students of SMP Negeri 1 Barru for the 2022/2023 academic year.